PEMECAHAN MASALAH PEMBELAJARAN MATEMATIKA BERORIENTASI KURIKULUM CAMBRIDGE DI ERA PANDEMI COVID-19 - Sinta Fitriana; Sutama (LPPM Universitas Bina Bangsa, 2021)
21st-century literacy is very important in education. Critical thinking skills are one indicator of literacy. Regarding thinking skills, it cannot be separated from solving mathematical problems. This study aimed to describe the problem solving of mathematics learning oriented to the Cambridge curriculum in the Covid 19 pandemic era. This research method is descriptive qualitative research. While the data collection technique uses interview techniques and questionnaires via a google form. This study found that students who understand Cambridge mathematics material obtained 79.4% based on interviews and questionnaires. Students who do not understand the concept of the material 21.2%. Students make completion steps. The percentage results show that 57.1% while the remaining 42.9% of students sometimes use completion steps. Students can complete the counting operation by 67%. While the remaining 33% still have difficulty calculating. The percentage of students who re-checked the process and results were 94.3%, while the rest often did not check the process and results